2021
DOI: 10.1259/bjr.20201151
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular interventions in management of renal artery aneurysm

Abstract: Renal artery aneurysm is a rare disease. With modern non-invasive imaging modalities, the disease is being increasingly diagnosed. It is a slow-growing aneurysm with high mortality in the event of rupture; especially in pregnant females and patients with multiple comorbidities. Traditionally, aneurysms located in the main renal artery had been successfully treated with endoprosthesis but technical limitations existed in more distal locations where patients were treated surgically. With advances in endovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Therefore, stent grafts are not recommended for renal aneurysms with small blood vessels (<6 mm) or curved vessels (32). Selective coil embolization is also commonly used for saccular aneurysms with a neck diameter of <4 mm or an aneurysm-toneck ratio of 2:1 (33). Type II aneurysm: Due to the special anatomy and location of Type II aneurysms, intravascular interventional therapy is challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, stent grafts are not recommended for renal aneurysms with small blood vessels (<6 mm) or curved vessels (32). Selective coil embolization is also commonly used for saccular aneurysms with a neck diameter of <4 mm or an aneurysm-toneck ratio of 2:1 (33). Type II aneurysm: Due to the special anatomy and location of Type II aneurysms, intravascular interventional therapy is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Type II aneurysm: Due to the special anatomy and location of Type II aneurysms, intravascular interventional therapy is challenging. Open vascular surgery, such as external reconstruction, autotransplantation, and nephrectomy, is the standard treatment for fusiform aneurysms in the main renal artery or large segment artery, such as external reconstruction, autotransplantation, and nephrectomy (22,33). Some studies reported that multilayer stents have been used successfully to treat complex renal aneurysms (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late postoperative complications included stent stenosis, renal artery thrombosis, renal bypass thrombosis, post-embolization syndrome, and chronic abdominal abscess. [19] Ghosh and Dutta [21] analyzed 14 published studies in which 157 RAAs were treated. The most commonly reported complications are renal infarction (15%), postembolization syndrome (leukocytosis, fever, abdominal pain, nausea and vomiting) (5%), coil migration into the native renal artery compromising a significant area of the renal parenchyma (1.2%), and aneurysm sac expansion reperfusion (<1%).…”
Section: Potential Complications Outcome and Follow-upmentioning
confidence: 99%